Using nasal sprays to prevent respiratory tract infections: a qualitative study of online consumer reviews and primary care patient interviews. Issue 6 (30th June 2022) - Williamson, Sian; Dennison, Laura; Greenwell, Kate; Denison-Day, James; Mowbray, Fiona; Richards-Hall, Samantha; Smith, Deb; Bradbury, Katherine; Ainsworth, Ben; Little, Paul; Geraghty, Adam W A; Yardley, Lucy
Abstract : Objectives: Nasal sprays could be a promising approach to preventing respiratory tract infections (RTIs). This study explored lay people's perceptions and experiences of using nasal sprays to prevent RTIs to identify barriers and facilitators to their adoption and continued use. Design: Qualitative research. Study 1 thematically analysed online consumer reviews of an RTI prevention nasal spray. Study 2 interviewed patients about their reactions to and experiences of a digital intervention that promotes and supports nasal spray use for RTI prevention (reactively: at 'first signs' of infection and preventatively: following possible/probable exposure to infection). Interview transcripts were analysed using thematic analysis. Setting: Primary care, UK. Participants: 407 online customer reviews. 13 purposively recruited primary care patients who had experienced recurrent infections and/or had risk factors for severe infections. Results: Both studies identified various factors that might influence nasal spray use including: high motivation to avoid RTIs, particularly during the COVID-19 pandemic; fatalistic views about RTIs; beliefs about alternative prevention methods; the importance of personal recommendation; perceived complexity and familiarity of nasal sprays; personal experiences of spray success or failure; tolerable and off-putting side effects; concerns about medicines; and the nose as unpleasant and unhygienic. Conclusions: People who suffer disruptive, frequent or severe RTIs or who are vulnerable to RTIs are interested in using a nasal spray for prevention. They also have doubts and concerns and may encounter problems. Some of these may be reduced or eliminated by providing nasal spray users with information and advice that addresses these concerns or helps people overcome difficulties.